Human Values and Religion: Semi-Automatic Human Values Systems Analysis for Religious Institutional Diagnostics. Issue 29 (2016) - Stapleton, Larry; Marques, Dawton
Abstract: Systematic analyses of the values of religious movements have not received much attention in the control and automation literature. Utilizing a theory of universal value types from the social sciences this paper presents a semi-automatic system for assessing institutional cultural values and leadership values in a religious community. It sets out findings gathered from a large Pentecostal community in Brazil revealing incongruences between leadership and laity value systems in the target community. Tests showed that this semi-automatic system was capable of gathering, processing and presenting robust values congruency data in a usable way to religious leaders and other interested parties. The implications are that it is now possible to build (semi) automatic systems to analyse institutional values and expose deep cultural values which may be out of alignment with the espoused values of the religious movement. Implications are drawn for control systems research and future research directions presented.